2007
DOI: 10.1097/hjh.0b013e328013e805
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endothelial nitric oxide synthase by red wine polyphenols: impact of grape cultivars, growing area and the vinification process

Abstract: The biological activity of red wines on eNOS transcription depends neither on grape cultivars nor on growing area in general. Resveratrol may be the most promising ingredient in red wine polyphenol extracts, but does not account for the complete effect. A large part of the active components are genuine grape compounds, since extracts of grape juice that did not undergo a fermentation process also showed activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 31 publications
1
23
1
1
Order By: Relevance
“…Similarly, other studies confirmed that high concentrations of resveratrol significantly enhanced eNOS gene expression and enzyme activity, and hence NO production, in in vitro assays (Räthel et al, 2007;Appeldoorn et al, 2009). In contrast, Nicholson et al (Nicholson et al, 2010) reported that exposure of HUVECs to nanomolar concentrations of resveratrol for 24 h increased the eNOS mRNA level, although eNOS protein and NO production were not affected.…”
Section: Effects Of Resveratrol On Antioxidant Mechanisms Protecting supporting
confidence: 50%
“…Similarly, other studies confirmed that high concentrations of resveratrol significantly enhanced eNOS gene expression and enzyme activity, and hence NO production, in in vitro assays (Räthel et al, 2007;Appeldoorn et al, 2009). In contrast, Nicholson et al (Nicholson et al, 2010) reported that exposure of HUVECs to nanomolar concentrations of resveratrol for 24 h increased the eNOS mRNA level, although eNOS protein and NO production were not affected.…”
Section: Effects Of Resveratrol On Antioxidant Mechanisms Protecting supporting
confidence: 50%
“…71) However, their experiments were not conducted under dietary conditions, as the biological activity of resveratrol was observed between 10 and 100 μM. Räthel et al 82) and Appeldoorn et al 83) confirmed that resveratrol at high concentrations significantly enhanced eNOS gene expression and enzyme activity, and NO production. In contrast, Nicholson et al 84) reported that the exposure of HUVECs to nanomolar concentrations of resveratrol for 24 h increased the eNOS mRNA level, although neither eNOS protein nor NO production were determined.…”
Section: Link To Enosmentioning
confidence: 90%
“…Longterm resveratrol exposure results in the increased expression of endothelial nitric oxide synthase (eNOS) in cultured endothelial cells, and this is involved in nitric oxide (NO)-mediated relaxation of blood vessels. [3][4][5] Some groups have reported that bolus treatment with resveratrol reduces vascular tone in isolated rings of the aorta and coronary artery, and endothelial NO might mediate the acute dilating effect of resveratrol. [6][7][8] Wallerath et al 3) reported that resveratrol might rapidly increase NO production in cultured endothelial cells; however, in their study, neither NO nor its metabolites were directly measured, and the effective concentrations of resveratrol were comparatively high.…”
mentioning
confidence: 99%